ANALYSIS OF FACTORS AFFECTING INCREASING PRODUCTION EFFICIENCY IN INDUSTRIAL ENTERPRISES (Marketing Journal, 2025)
This article comprehensively examines the enhancement of industrial enterprise efficiency and the significance of advanced technologies and innovative approaches in this process. The impact of digital transformation, artificial intelligence, automation, innovative materials, and marketing strategies on industrial sector development is analyzed. The study highlights that the integration of IoT, AI, cloud technologies, and innovative materials such as HEAs and LPBF plays a crucial role in improving industrial productivity. The efficiency of industrial enterprises is assessed based on material resources, intangible assets, labor resources, and entrepreneurial capabilities. The findings indicate that to increase industrial sector comp etitiveness and economic efficiency, as well as to facilitate the adoption of innovations, it is essential to widely implement digital technologies. The article presents scientific proposals and practical recommendations for improving industrial efficiency .
Keywords: industrial efficiency; digital transformation; artificial intelligence; automation; innovative materials; marketing strategies; IoT; HEAs; LPBF